The Contribution of Common UGT2B10 and CYP2A6 Alleles to Variation in Nicotine Glucuronidation among European Americans - Bloom, A. Joseph (2013)
UDP-glucuronosytransferase-2B10 (UGT2B10) is the primary catalyst of nicotine glucuronidation. To develop a predictive genetic model of nicotine metabolism, the conversion of deuterated (D(2))-nicotine to D(2)-nicotine-glucuronide, D(2)-cotinine, D(2)-cotinine-glucuronide, and D(2)-trans-3'-hydroxycotinine were quantified in 188 European Americans, and the contribution of UGT2B10 genotype to variability in first-pass nicotine glucuronidation assessed, following a procedure previously applied to nicotine C-oxidation. The proportion of total nicotine converted to nicotine-glucuronide (D(2)-nicotine-glucuronide/ (D(2)-nicotine +D(2)-nicotine-glucuronide +D(2)-cotinine +D(2)-cotinine-glucuronide +D(2)-trans-3'-hydroxycotinine)) was the primary phenotype. The variant, rs61750900T (D67Y) (minor allele frequency (MAF) = 10%), is confirmed to abolish nicotine glucuronidation activity. Another variant, rs112561475G (N397D) (MAF = 2%), is significantly associated with enhanced glucuronidation. rs112561475G is the ancestral allele of a well-conserved amino acid, indicating that the majority of human UGT2B10 alleles are derived hypomorphic alleles. CYP2A6 and UGT2B10 genotype explain 53% of the variance in oral nicotine glucuronidation in this sample. CYP2A6 and UGT2B10 genetic variants are also significantly associated with un-deuterated (D(0)) nicotine glucuronidation in subjects smoking ad libitum. We find no evidence for further common variation markedly influencing hepatic UGT2B10 expression in European Americans.